A Survey on Knowledge of Registered Drugs amongst Patients from the Specialist Clinic, Malaysia - Wahida Zulkifli, Nur; Amir Mohd Yunus, Mohd; Fakarul Radzi Mohamed Mustafa, Mohd; Wei En, Kong; Chong Yee, Lim; Weng Hong, Ng; Rubinee Povanesvaran, Nethiya; Zainal , Zalinur (Al-Nahrain Journal of Science, 2019)
Introduction: One of the solutions to reduce unregistered drugs usage is via awareness and educational programmes. The aim of this study is to determine the significance difference of patients’ level of knowledge between control and intervention groups towards registered drugs. Method: The study used a pre- and post-test by answering the validated survey during October-November 2018 at a tertiary hospital in Malaysia. It has two groups as an intervention group (IG) receiving counseling and control group (CG) which did not receive any counseling. This study used systematic random sampling. The data analysis was performed using SPSS version 23. Descriptive data was reported, including the answers each question, score, level of knowledge based on the percentages and the socio-demographic data. The pre and post differences of the score between control and intervention groups were assessed using ANCOVA. Result: A total of 657 respondents were obtained which overall response rate of 93%). Majority of the participants are aged between 18-28 years old (47%), female (58.3), Malay (47.4%), Degree holder (69.1%) and in the government sector (38.3%). However, the majority of participants are in the category of the acceptable level of knowledge towards registered drugs (40.8%) and only 3.5% of the participants are in the category of excellent. However, about 66.1% of the participants have scored above 50%. It can be considered that the majority of the participants have knowledge about registered drugs. IG group displayed significantly higher post-test results compared with CG group (p<0.001). Conclusion: The used of the validated survey during the awareness programmes might give benefit to the public who attends the awareness and educational programmes and finally can improve the effectiveness of the programmes in the future. In the future, the improvement of the design of the campaign might include the use of a survey in order to give more understanding to the public towards registered drugs.